Local Flap Reconstructions in Oral Cavity Defects: An Insight from 104 Cases - Poonam Joshi; Manasi Bavaskar; Rathan Shetty; Arjun Singh; Sudhir Nair; Pankaj Chaturvedi (Rambam Maimonides Medical Journal, 2024)
Background: Resection of oral cavity carcinoma often leads to complex defects causing functional and aesthetic morbidity. Providing optimum reconstruction with free flaps becomes challenging in a high-volume center setting with constrained resources. Hence, understanding the local flap technique for reconstructing oral cancer defects is prudent.